1968
DOI: 10.3758/bf03331220
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the behavioral and biochemical effects of electroconvulsive shock with nicotine

Abstract: Mice treated with nicotine sulfate (J.O mg/k g, i.p.) prior to training for a passive avoidance response showed antagonism toward the amnesic effect produced by a post-training electroconvulsive shock; this effect was particularly apparent when drug treatment was given 45 to 60 min prior to training. A reversal of the predicted effect of ECS upon brain serotonin level by nicotine suggested a possible CO"oiary of the drug-induced facilitation of memory consolidation.Prior studies have indicated' that the admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1971
1971
1981
1981

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As summarized in Table I, the incidence of passive avoidance acquisition among aggregated mice was not significantly altered by prior treatment with nicotine sulfate (as previously indicated : Essman et al, 1968;Essman and Essman, 1971), however, the lower incidence of passive avoidance acquisition by isolated mice was significantly increased by nicotine treatment. Active avoidance response latency or escape response latency during the active avoidance training trials was not altered by either housing condition or drug treatment.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…As summarized in Table I, the incidence of passive avoidance acquisition among aggregated mice was not significantly altered by prior treatment with nicotine sulfate (as previously indicated : Essman et al, 1968;Essman and Essman, 1971), however, the lower incidence of passive avoidance acquisition by isolated mice was significantly increased by nicotine treatment. Active avoidance response latency or escape response latency during the active avoidance training trials was not altered by either housing condition or drug treatment.…”
Section: Resultsmentioning
confidence: 53%
“…In previous reports (Essman et al, 1968;Essman and Essman, 1971) we have indicated that passive avoidance acquisition and retention was not notably altered by nicotine sulfate. The effects of the drug upon active avoidance conditioning is, in one respect, comparable with results obtained by Bovet et al (1966) and Bovet and Bovet-Nitti (1965); in these experiments a lower parented dose of nicotine sulfate facilitated avoidance acquisition among initially poor avoidance performing mice, while it impaired such acquisition among mice showing high avoidance performance.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although the physiological effects of smoking tobacco have been extensively studied in both man and animals (Rothe et aZ., 1944; Larson et al., 1961;Domino, 1967;Essman et al, 1968;Frankenhaeuser et al, 1968Frankenhaeuser et al, , 1969Frankenhaeuser et al, , 1970, few experimental studies have been made of changes in human performance that may ensue from smoking tobacco. Performance changes following smoking do occur ; Cotten et al (1971) found changes in simple reaction time following smoking, and repeated performance of a visual-search task is impaired (Johnston, 1966).…”
mentioning
confidence: 99%